Systematic Literature Review: STEM Approach through Engineering Design Process with Project Based Learning Model to Improve Mathematical Creative Thinking Skills - Maydilla Fadiarahma Vistara; Rochmad Rochmad; Kritina Wijayanti (Department of Mathematics Education University of Muhammadiyah Malang, 2022)
The STEM approach is a learning approach that allows students to think creatively. Creative thinking is included in the skills of the 21st century, especially the 4C ability that students must have to be able to compete globally. This research aims to describe the STEM approach through EDP with the PjBL model and examine the impact of implementing STEM approaches through EDP with the PjBL model on students' creative thinking skills. This research is qualitative research conducted using literature studies. Data collection in this study was carried out by reviewing articles in national and international journals. STEM-EDP implementation with project-based learning can be done in group learning. The results of the study by referring to previous research related to STEM-EDP with project-based learning can be concluded that STEM-based project-based engineering through engineering design processes are able to provide influence to improve students' creative thinking skills.